2017
DOI: 10.1248/bpb.b16-00765
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Analysis of Hepatitis B Virus Reactivation-Induced Hepatitis B Using JADER

Abstract: Hepatitis B caused by chemotherapy-and immunosuppression-associated hepatitis B virus reactivation is likely to become fulminant, and a high mortality rate has been reported. In this study, using the Japanese adverse drug event report database (JADER), factorial analysis of patients who developed hepatitis B as an adverse event was performed. The number of reported cases of hepatitis B during the survey period was 781 and 185 of them (24%) died. Rituximab and prednisolone were administered to many cases (233, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Bohnert et al reported that among patients receiving opioid prescriptions for pain, a higher morphine equivalent dose of ≥100 mg/d was associated with an increased risk of opioid overdose-related death. 29) As shown in Fig. 2, the median daily dose of transdermal fentanyl was 120 mg of oral morphine equivalent, whereas the oral morphine and oxycodone doses were comparably low (30 mg of oral morphine equivalents).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Bohnert et al reported that among patients receiving opioid prescriptions for pain, a higher morphine equivalent dose of ≥100 mg/d was associated with an increased risk of opioid overdose-related death. 29) As shown in Fig. 2, the median daily dose of transdermal fentanyl was 120 mg of oral morphine equivalent, whereas the oral morphine and oxycodone doses were comparably low (30 mg of oral morphine equivalents).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, several studies reported that patients using opioids with a daily morphine equivalent dose as low as 20 to 50 mg can also experience life-threatening respiratory or CNS depression under impairment of hepatic or renal function, or concomitant use of CNS depressants such as benzodiazepines, antidepressants, and alcohol. 27,29) The usefulness of the Weibull distribution for profiling the time-to-onset of ADEs has been reported. 11,12,[30][31][32] To the best of our knowledge, no time-to-onset analysis of respiratory depression for opioids in cancer patients has been done using SRSs.…”
Section: Discussionmentioning
confidence: 99%
“…An automated reporting system is needed to obtain data for a database with an aim for reducing cost and labor . In the United States, Korea, and Japan, the signal detection for adverse events was investigated using databases, including spontaneous adverse event reporting databases . The US Food and Drug Administration launched the “Sentinel Initiative” to expand postmarketing safety data analysis, which is still investigational, especially for anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the United States, Korea, and Japan, the signal detection for adverse events was investigated using databases, including spontaneous adverse event reporting databases. [24][25][26][27] The US Food and Drug Administration launched the "Sentinel Initiative" to expand postmarketing safety data analysis, 28 which is still investigational, especially for anticancer drugs. Careful analysis between the costs of creating extremely large databases and obtaining meaningful clinical information must also be conducted.…”
Section: All-case Surveillance Of Oncology Drugs In Japanmentioning
confidence: 99%
“…In Japan, the Pharmaceutical and Medical Device Agency (PMDA) has collected spontaneous adverse event reports of drugs for medical use, non-prescription drugs, and drugs requiring guidance since 2004, and more than 300000 adverse event reports are open to the public as the Japanese Adverse Drug Event Report (JADER). JADER has been utilized in many retrospective studies, [1][2][3] playing a major role in the safety evaluation of drugs in clinical practice sites in Japan. 4) The U.S. Food and Drug Administration (FDA) opened the FDA's Adverse Event Reporting System (FAERS) to the public, which is also a spontaneous adverse event report database similar to JADER.…”
Section: Introductionmentioning
confidence: 99%